Malignant glomus tumor of the gastric antrum with hepatic metastases: a case report and literature review - Adina A. Bodolan; Rebecca Wilcox; Michelle X. Yang (Elsevier, 2018)
Glomus tumor (glomangioma) is an uncommon pericytic neoplasm derived from glomus cells, which are modified smooth muscle cells of the glomus body. Malignant glomus tumors (glomangiosarcomas) are extremely rare mesenchymal neoplasms. There are limited reports of metastatic malignant glomus tumors within the gastrointestinal tract in the literature. We report a case of an 80-year-old woman who presented with vague epigastric discomfort. On computed tomography (CT) imaging, a 7.1 cm solid enhancing mass was seen originating from the gastric antrum and was clinically suspected to be a gastrointestinal stromal tumor (GIST). Needle core biopsies were obtained from the antral mass and demonstrated an epithelioid neoplasm with a brisk mitotic activity. The morphology and imunohistochemical profile (CKIT/DOG1 negative and strong immunoreactivity with smooth muscle actin), was consistent with a malignant glomus tumor, at least FNCLCC grade 2. At the time of the planned gastric resection, multiple hepatic metastases were identified and confirmed on frozen section to be consistent with metastatic malignant glomus tumor. Keywords: Malignant glomus tumor, Antrum, Metastasis, Liver